Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1073/pnas.0608134104
|View full text |Cite
|
Sign up to set email alerts
|

The role of mantle ultrapotassic fluids in diamond formation

Abstract: Analysis of data on micro-and nano-inclusions in mantle-derived and metamorphic diamonds shows that, to a first approximation, diamond-forming medium can be considered as a specific ultrapotassic, carbonate/chloride/silicate/water fluid. In the present work, the processes and mechanisms of diamond crystallization were experimentally studied at 7.5 GPa, within the temperature range of 1,400 -1,800°C, with different compositions of melts and fluids in the KCl/K 2CO3/H2O/C system. It has been established that, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(38 citation statements)
references
References 63 publications
(82 reference statements)
2
36
0
Order By: Relevance
“…The absence of any evidence for an accumulation of this kind of melts at the base of the lithosphere, where temperatures would be low enough for complete crystallization of the carbonatite melts, suggests that a redox reaction with the reduced mantle (Frost and McCammon 2008;Rohrbach et al 2009) immobilizes these carbonatites. In fact, diamond crystallization has been shown to be favored by the catalytic behaviour of K 2 CO 3 -rich melt and fluid (Taniguchi et al 1996;Palyanov et al 2007;Klein-BenDavid et al 2007).…”
Section: Evidence For Subducted Carbonates and K-rich Metasomatism Inmentioning
confidence: 99%
“…The absence of any evidence for an accumulation of this kind of melts at the base of the lithosphere, where temperatures would be low enough for complete crystallization of the carbonatite melts, suggests that a redox reaction with the reduced mantle (Frost and McCammon 2008;Rohrbach et al 2009) immobilizes these carbonatites. In fact, diamond crystallization has been shown to be favored by the catalytic behaviour of K 2 CO 3 -rich melt and fluid (Taniguchi et al 1996;Palyanov et al 2007;Klein-BenDavid et al 2007).…”
Section: Evidence For Subducted Carbonates and K-rich Metasomatism Inmentioning
confidence: 99%
“…A similar effect will be produced by H 2 O-CO 2 fluids (40-42). It was experimentally shown that the addition of these components in the system significantly increases the diamondforming ability of mantle fluids/melts (43,44), acting in the oxidized conditions behind the redox front. Under reducing conditions, ahead of the redox front, where the diamond crystallized from Fe-C melt only, the presence of H 2 O will lead to the inhibitory effect on the diamond-forming process (45).…”
Section: Significancementioning
confidence: 99%
“…Thus, the molten K 2 CO 3 may also have high electrical conductivity, which can also contribute to high mantle conductivity. In addition, analyses of microinclusions in diamond (e.g., Sobolev et al, 1998;Hwang et al, 2006) and diamond-formation experiments (e.g., Pal'yanov et al, 1999Pal'yanov et al, , 2007 indicate that the composition of the diamond-forming medium can be roughly considered as ultrapotassic carbonate fluid. Considering the low melting temperature of K 2 CO 3 , we suggest that the existence of K 2 CO 3 -rich liquid may contribute to the formation of diamond in the mantle.…”
Section: Melting Of Carbonates At High Pressurementioning
confidence: 99%